An American in Warsaw Selected Writings of Hugh S. Gibson, US Minister to Poland, 1919-1924 - Gibson, Hugh, 1883-1954 (Book collections on Project MUSE., 2018)
"Hugh Gibson, US Minister to Poland from 1919 to 1924, recorded his involvement with the rocky first years of Polish statehood in this collection of official dispatches and personal letters."--Provided by publisher.